The relationship between macroeconomic variables with stock market price in Malaysia / Nursheena Mohamad Norizan - Mohamad Norizan, Nursheena (2014)
This study examines the factor affecting Kuala Lumpur Composite Index (KLCI) volatility in Malaysia. KLCI shows performance of the stock market and also economic growth in Malaysia. Analyzing the sources of volatility in this selected stock market price (KLCI) is for implications regarding asset allocation, risk management and also for portfolio selection. Based multiple regression model, this thesis examines the factors of three (3) macroeconomic factors which are interest rate, inflation and GDP. It shows that most the macroeconomic factors statistically significant. The findings support the expected hypotheses that interest rate, inflation and GDP are the factor volatility stock market in Malaysia. The variables which are positive relationship with KLCI are inflation rate and GDP. Meanwhile interest rate is negative relationship with KLCI. This study used quarterly data over 2002 to 2012 period and regress those data by using E-Views. KLCI shows performance of the stock market and the economic growth in Malaysia as well. This research was conducted in order to measure the applicability of other previous researches. This study was conducted to acquaint the movement of the macroeconomic variables over 11 years period from 2002 until 2012 on quarterly basis. There were two methods in measuring the findings which is single linear regression and multiple linear regressions. The findings support the expected hypotheses that inflation rate and gross domestic product are the factor that affect KLCI stock market price in Malaysia. The variables show positive relationship which means when inflation rate rise, the stock market price will also rises. Meanwhile the interest rate shows negative relationship with KLCI stock market in Malaysia. Conclusion from the research is, these result further our understanding of the relationship between the macroeconomic variable towards stock market price and should be useful for policy maker, investor and speculator.